Collaborative negotiation for ontology-driven enterprise businesses - Jardim-Goncalves, R.; Coutinho, C.; Cretan, A.; Ferreira da Silva, C.; Ghodous, P. (Computers in Industry, 2014)
The requirements from a globalised world demand that enterprises not only shift their paradigm from product-centrism to component-centrism on integrated products, potentiating the need for tight interoperability dependencies, but also that the products specifications and concepts are fully understood by customers and providers in a transparent manner that surpasses the barriers of language, culture and technology. This paper presents the NEGOSEIO framework, which enables service-based interoperability between parties, closely integrated with semantics and business understanding via the use of reference ontologies in the quest for achieving a stronger interoperability liaison. The paper’s validation and discussion is performed in its application on the ontology negotiation of business environments in the scope of the EU-funded FP7 project TIMBUS for digitally preservation of resources and enduring business continuity.